(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The Egyptian scholar Muhammad Juyushi, who has studied the legacy of the scholar in detail, also draws attention to this issue and points out that although al- Hakim al-Tirmidhi did not write an independent work on Kalam, the author’s denials to the various sects from the point of view of the Ahl asSunnah reflects on some of the shortcomings of the Rafidhis’ beliefs, such as "ar-Radd alar-Rafidha" and "ar-Radd alal-Muattila," which were written as a refutation of the Mu’attila sect